SOCIAL DEVELOPMENT, CONTEMPORARY REFORMS, AND THE CULTURAL–EDUCATIONAL TRANSFORMATION IN UZBEKISTAN (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This article explores the multidimensional reforms taking place in Uzbekistan and analyzes how these changes influence social life, cultural institutions, and the educational landscape. Particular attention is given to the development of cinema, theatre, and museums, as well as the evolving role of sports in national identity building. The study also highlights the contribution of distinguished Uzbek athletes to the development of the education system and youth policy. By examining recent state strategies, cultural modernization, and sport–education integration, the article provides a comprehensive understanding of Uzbekistan’s ongoing transformation in the context of global socio-cultural trends. These reforms reflect a holistic approach that seeks to harmonize tradition and modernity while addressing the needs of an increasingly globalized society.